Impact of posttraumatic stress syndrome on GPA For Yazidi students studying at Duhok Polytechnical University - Younes MoradAlibrahim, MSc. Mohamed Sadeq (International Journal of Psychosocial Rehabilitation, 2024)
This study shows the impact of post-traumatic syndrome on the cumulative rate ofstudents studying at Duhok Polytechnic University. The 314 students from differentlevels at Duke Polytechnic University are targeted randomly selected. In order toanswer the hypotheses of the study, the computational averages, the Pearsoncorrelation coefficient, and the use of the T-test were used where the results indicatedthe following: The increase in post-traumatic syndrome is associated with an increasein mental unit feeling. The level of mental unity is higher in the group of two sourcescompared to the group of non-traumatized people. The existence of statisticaldifferences between males and females in the level of the post-traumatic syndrome,and this is higher among females. The existence of statistical differences betweenmales and females in the low cumulative rate of male and female enrollment and thisis higher for females. In the light of the results, a number of recommendations andproposals have been formulated that could contribute to improving student copingwith a post-traumatic syndrome, improving the cumulative rate and improving socialcommunication.